PENDIDIKAN AGAMA PADA ANAK MUCIKARI DI LOKALISASI GAMBILANGU MANGKANG SEMARANG - Saiful Aziz (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
Education is recognized as a force that can help the Society achieve the splendor andprogress of civilization. Religious education directly touches the very essence of theessence of the students, especially in terms of values, attitudes, and practice of religion.Education will provide positive values, attitudes, and demands of behavior and religiousexamples. The more religious experience, and the more religious elements, the attitudesand actions, behavior and way of dealing with life will be in accordance with theteachings of religion.This study aims to find and describe the profile of pimp children, the forms of religiouseducation obtained by pimp children and the experience of pimping children's education.Based on the above description, the authors emphasize the following issues: (1) Where dopimp kids get religious education? (2)What aspects of religion do pediatric children gainin religious education in pimp children in the localization of gambilangu MangkangSemarang?This study uses a qualitative approach, a study that seeks to reveal the state of a naturalnature as a whole.Qualitative research is used to understand the community, problemsand symptoms by collecting as much as possible facts that can be observed. The methodused is descriptive method that aims to describe the problem systematically.Islamic education in pimpchildren in lokalisasi gambilangu mangkang semarang has runalthough not ideal yet. Pimped children receive Islamic Education in schools (Primaryand Kindergarten), Qur'anic Education Park and Village Neighbor's mosque and someare in Musolla (the only localized musolla). From these educational institutions pimpchildren get knowledge about aqidah / faith, worship and morals.Keywords: Education,Pimps,Child,Localization.